Role of Endoscopic Procedures in the Diagnosis of IgG4-Related Pancreatobiliary Disease - Jung, Ye-Ji; Moon, Sung-Hoon; Kim, Myung-Hwan (Chonnam medical journal, 2021)
The emergence of the disease entity of glucocorticoid-responsive systemic immunoglobulin G4 (IgG4)-related pancreatobiliary disease has generated substantial attention among the international gastroenterology society. IgG4-related pancreatobiliary disease includes type 1 autoimmune pancreatitis (AIP) and IgG4-related sclerosing cholangitis (IgG4-SC). The typical manifestations of IgG4-related pancreatobiliary disease are cholestatic liver dysfunction, obstructive jaundice, and weight loss, although it may present with no clinical symptoms. Since it mimics tumors on imaging, AIP/IgG4-SC may often be misdiagnosed as pancreatic or biliary cancer. The endoscopic armamentarium for the diagnosis of IgG4-related pancreatobiliary disease includes endoscopic ultrasonography, intraductal ultrasonography, endoscopic retrograde cholangiopancreatography, and cholangioscopy. The role of endoscopic tissue acquisition is two-fold in the diagnosis of IgG4-related pancreatobiliary disease: exclusion of cancer and procurement of histopathological proof for diagnosis of AIP/IgG4-SC, which can also be achieved by adding the immunohistochemistry for IgG4. Our review article addresses the role of various endoscopic examinations in diagnosing IgG4-related pancreatobiliary disease, focusing on the differentiation of this condition from pancreatobiliary malingnancies.